Islam, Human Rights, and AKP (Adalet ve Kalkinma Partisi) in Turkey - Afwan Faizin; Ali Mansur; Akhmad Mughzi Abdillah (AHKAM : Jurnal Ilmu Syariah, 2021)
The article aims to describe the influence of the political strengthening of the Turkish Islamist party, AKP (Adalet ve Kalkınma Partisi, Justice and Development Party) on human rights legislation in Turkey's national legislation. The research was conducted in Turkey in 2019 with a qualitative approach. Data collection techniques are in-depth interviews, literature studies, and focused groups discussion. The findings of the study conclude that although Islamic norms do not formally influence Turkey's human rights legislation, the strengthening of Islamist parties in Turkey “influences” the human rights legislation process in Turkey. An example is the failure of a bill to protect LGBT people proposed by the secular-Kemalist party, CHP (Cumhuriyet Halk Partisi, Republican People's Party) caused by the majority of seats in the Turkish parliament controlled by the AKP. As a result, Turkey's membership in the European Union (EU) has not been accepted because several EU human rights protocols have not been ratified in Turkey's human rights legislation. The study shows that the view of AKP on human rights is not compatible with the universal human rights.    Abstrak: Artikel ini menjelaskan pengaruh menguatnya politik partai Islamis Turki AKP (Adalet ve Kalkınma Partisi, Justice and Development Party) terhadap legislasi HAM pada perundang-undangan nasional Turki. Penelitian ini dilakukan di Turki pada 2019 dengan pendekatan kualitatif. Teknik pengumpulan data adalah wawancara mendalam, studi literatur, dan Focussed Groups Discussion (FGD). Temuan penelitian ini menyimpulkan bahwa meski legislasi HAM Turki secara formal tidak dipengaruhi oleh norma-norma Islam, tapi menguatnya partai Islamis di Turki “berpengaruh” terhadap proses legislasi HAM di Turki. Sebagai contoh adalah kandasnya rancangan undang-undang yang bertujuan melindungi kelompok LGBT yang diusulkan oleh partai sekular-Kemalis, CHP (Cumhuriyet Halk Partisi, Republican People’s Party). Rancangan itu ditolak oleh mayoritas kursi parlemen Turki yang dikuasai oleh AKP. Akibatnya, hingga saat ini, keanggotaan Turki di Uni Eropa belum diterima karena beberapa protokol HAM Uni Eropa belum diratifikasi dalam legislasi HAM Turki. Studi ini menunjukkan bahwa penafsiran AKP tentang HAM tidak sesuai dengan gagasan universal HAM.